Manganese–calcium clusters supported by calixarenes - Fuller, Rebecca; Koutsantonis, G.; Lozic, I.; Ogden, Mark; Skelton, B. (R S C Publications, 2015)
The structure of the oxygen-evolving complex of photosystem II, which contains a cubane-like metal-oxo cluster incorporating four manganese (III,IV) cations, along with a calcium cation, has focussed attention on synthetic analogues of this cluster. Despite this activity, there are relatively few structurally characterised coordination clusters with this combination of metal cations. The calixarenes are synthetically versatile and well established cluster-supporting ligands, which to date have not been reported to support a calcium/manganese cluster. Here we report that p-t-butylthiacalix[4]arene supports CaMn2 and Ca2Mn2 clusters, whereas reactions of p-t-butylcalix[4]arene, p-t-butylsulfinylcalix[4]arene, and p-t-butylsulfonylcalix[4]arene, under the same conditions, produced only homometallic manganese complexes.